Mammalian Diversity of Gunung Ledang, Johor, Peninsular Malaysia - Faiznur Ain Ahmad Bakri; Masatoshi Yasuda; Maryati Mohamed; Adlil Ikram Sharuddin; Muhazam Syah Hambar (HAYATI Journal of Biosciences, 2020)
Mammals play a crucial role for the biotic processes of the rainforest ecosystem. Studying their behaviour and biology are vital to fully understand the jigsaw of rainforest dynamics. This study was made to update the diversity checklist of mammals in Gunung Ledang. This study was done in Taman Negara Johor; Gunung Ledang (2.37°N, 102.60°E) where it is known to be the highest mountain (1,276 m asl.) in the southern Malay Peninsula. This study was conducted from July 2018 to April 2019. In total, 22 cameras were installed along three nature trails which are Sagill trail, Telekom Trail, and Resort Trail. Overall, a total of 31 species of terrestrial mammals from small- to large-sized were recorded in our camera trapping study of 3434 camera-days.Mammals such as the Leopard (Panthera pardus), Sumatran Serow (Capricornis sumatraensis), and Malayan Tapir (Tapirus indicus) were caught in the videos of camera trap. This showed that the diversity of mammals in Gunung Ledang is quite high. Tthis paper already gave valuable insights in a rainforest guild that is highly diverse and of outstanding value to the forest ecosystem. Management plans and strategy to conserve the mammals in Gunung Ledang can be done as accordingly afterwards.